SERVICE QUALITY INNOVATION TO RETAIN CUSTOMERS SATISFACTION IN INDONESIAâS CAR-SHARING INDUSTRY (CASE STUDY AT PT. HIJAU MAJU) - Riendi Syauqi, Arga
The development of technology has been giving such a significant impact to life. The more advanced technology-based products like smartphones have been enabling people to not only connect but also do many things remotely such as web browsing, online shopping, and even completing daily needs with one click away. Several applications that assist people on their daily routines are available to use in a smartphone. One of the applications is an on demand service provider platform which enables people to order a transportation service, food delivery service, package delivery service, grocery shopping, and many more. Seeing this trend in countries abroad, PT. Hijau Maju started to offer their services by replicating the idea to apply in the Indonesian market. Starting to serve in 2010, the first product that PT. Hijau Maju offered to the market was a transportation service with a two-wheelers and four-wheelers unit. Expanding the business to four other countries in South-east Asia, the application has been downloaded more than one hundred fifty five million. The four-wheelers service of PT. Hijau Maju is still one of the core products that contribute a large amount of profit to the company.